The radiative flow of the thin-film Maxwell hybrid nanofluids on an inclined plane in a porous space - Gul, Taza; Mukhtar, Safyan; Alghamdi, Wajdi; Tag Eldin, Elsayed; Yassen, Mansour F.; Guedri, Kamel (Frontiers in Energy Research, 2022)
Due to their accelerated rate of heat transfer, nanofluids are of immense interest. This work analyzes an innovative concept of hybrid nanoemulsion with an optimized design under the chemical radiative flow and its thermophysical properties. We are able to achieve great aspects of the flow with the assistance of the sheet’s permeable texture and inclined surface. Furthermore, the effects of thermal conductivity mix convection, chemical reaction, and thermal radiations on velocity, temperature, and concentration fields are also investigated. After converting the fundamental equations to ordinary differential equations with the use of similarity transportation, the problem is then solved analytically with the HAM technique. To investigate key attributes and parameters, a hybrid nanofluid with Ag and Al2O3 nanoparticles as well as Al2O3 for conventional nanofluids with the base solvent water is taken. To illustrate the effects of chemical radiative and mix convection on the thin-film flow, numerous graphs, charts, and tables are shown. Calculations and reviews are performed for reduced friction coefficient, heat, and mass transportation. According to this study, hybrid nanofluids have a higher heat-transfer rate than nanofluids when exposed to thermal radiation and at the appropriate surface angle of inclination. Due to ϕAl2O3, ϕAg,S, Rd, the temperature increases, but velocity has the opposite effect. This investigation’s innovative findings will promote the study of condensed nanostructures and nanomaterials.